Quantifying the contribution of wind farms to distribution network reliability. (17th March 2014) - Blake, S.; Taylor, P.; Dent, C.; Miller, D.
Abstract: The reliability of power supply to distribution network customers can be increased by embedded generation, including wind farms. The value of this increase in reliability needs to be evaluated, and national standards such as the Great Britain security of supply standard P2/6 seek to do so. This paper appraises the capacity credit evaluation methodology in P2/6 and outlines an alternative methodology to integrate generation with load more effectively, taking into account the topology, loading and reliability of the surrounding network. It concludes that under certain circumstances, the presence of embedded wind generation can allow the deferral of costly network reinforcement projects but that the time for which reinforcement can reasonably be deferred is a function not only of the generators themselves but also of the surrounding network. Copyright © 2014 John Wiley & Sons, Ltd.